Media Sosial dan Kerukunan Umat Beragama di Bali (Representasi Masyarakat Bali terhadap Berbagai Posting Terkait Gerakan Aksi Damai terkait Isu Penistaan Agama di Media Sosial dan Dampaknya pada Kerukunan Umat Beragama di Bali) - Lukman Nusa (Universitas Muhammadiyah Surakarta, 2019)
AbstractThe character of social media causes the process of information’s dissemination becomes much more unimpeded. The freedom sometimes causes some parties forget about the importance of maintaining harmony among religious people. The are posts founded in the social media that lead to issues of SARA or in this research is related to the case of blasphemy committed by Ahok. The posts in some degree is being reputed as a common one, especially in the territory of Java which is dominated by moslem societies and for some parties it even becomes a necessity to express their voices to defend their religion, or so they say. Then the question is how the representation of Balinese society dominated by the non-moslem societies, react to the posts in Facebook related to the case. The theory of social representation by Moscovisci is used to answer the problem of representation. Case studies with data collection of in-depth interviews is used to analyze Balinese society representation about this issue.Keywords: representations, case study, social media, religious harmony